An explorative study of revenue models implemented by three South African news media companies to ensure the survival of their newsrooms in a post-COVID-19 world - Fild, Lucienne (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.